THE ROLE OF OPEN STANDARDS IN DIGITAL BUILDING PERMITTING, 3D REGISTRATION OF CONDOMINIUM, AND UPDATE OF 3D CITY MODELS - D. Guler; T. Yomralioglu (The International Archives of the Photogrammetry, Remote Sensing and Spatial Information Sciences, 2022)
Digitalization is being adopted in many public services to increase the efficiencies of the required operations. Regarding this, there is an important interest in digitalizing the current building permit procedures since most of the buildings are designed digitally and as three-dimensional (3D). In addition, several countries are making an effort to realize the transition from two-dimensional (2D) cadastre to 3D cadastre. This is because 2D delineation of the legal rights may remain incapable to reflect the reality with respect to property ownership in multipartite buildings. The 3D city models should also be kept updated to effectively manage the occasions (e.g., natural disasters) and services (e.g., waterworks) in the living areas. In this sense, the open data standards (e.g., CityGML and Industry Foundation Classes (IFC)) have a vital role to enable interoperability between different domains such as Architecture, Engineering, and Construction (AEC) and Land Administration (LA). In this context, this paper aims to show the current situation and opportunities on how to efficaciously benefit from open data standards for three significant issues. The issues can be listed as, 1) digitalizing the building permit procedures, 2) registering the condominium as 3D, and 3) updating the 3D city models. The examination in the paper concerns the cases for Turkey.